Synthesis and characterization of a hydrogen bonded metal-organic cocrystal: Exploration of its DNA binding study. (1st April 2020) - Khan, Samim; Alothman, Zeid Abdullah; Mohammad, Mukti; Islam, Md Sanaul; Slawin, Alexandra; Wabaidur, Saikh Mohammad; Islam, Md. Maidul; Mir, Mohammad Hedayetullah
Graphical abstract: A metal-organic cocrystal, [Co(2-quin)2 (3-ata)2 ]·[Co(2-quin)2 (H2 O)2 ] (1 ) (H2-quin = 2-quinalidic acid and 3-ata = 3-amino-1, 2, 4-triazole), has been synthesized, which shows significant hydrogen bonding interactions in the formation of a 2D supramolecular architecture. The cocrystal exhibits a good in vitro binding propensity with ctDNA, which was reflected by its high binding constant (Kb ) value of 2412 M −1 . A docking study has also been carried out to corroborate the experimental findings. Abstract: A metal-organic cocrystal, [Co(2-quin)2 (3-ata)2 ]·[Co(2-quin)2 (H2 O)2 ] (1 ) (H-2-quin = 2-quinalidic acid and 3-ata = 3-amino-1, 2, 4-triazole), has been synthesized and characterized by elemental analysis as well as the single-crystal X-ray diffraction (SCXRD) technique. Compound 1 crystallizes in the triclinic space group P ī and shows significant hydrogen bonding interactions, leading to the formation of supramolecular polymers. Hirshfeld surfaces analysis has been performed to investigate the non-covalent interactions in the crystal packing. The cocrystal shows a good in vitro binding propensity with ctDNA, which was reflected by its high binding constant (Kb ) value of 2412 M −1 . A docking study has also been carried out to corroborate the experimental findings.